2017
DOI: 10.1080/14733315.2017.1302658
|View full text |Cite
|
Sign up to set email alerts
|

Modelling natural ventilation for summer thermal comfort in Mediterranean dwellings

Abstract: There is an urgent need for adequate natural ventilation in apartment dwellers in densely built regions that could improve occupants' summer thermal comfort and reduce the rapidly increasing energy demand for cooling. The aim of the research reported here was to identify natural ventilation strategies that could offer energy efficient refurbishment solutions for domestic buildings whilst maintaining thermal comfort of occupants. An urban multi-storey apartment building in the city of Athens was selected for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Figure 21 provides a comparison of their expected performance. Empirical relationships were extrapolated and interpolated from a range of steady-state CFD results; these were in agreement with expected trends and could thus be used to predict ventilation performance behaviours under conditions that were not simulated (Spentzou et al, 2019). Higher wind speeds enhance the cooling performance of the cross-ventilation, wind-catcher, and dynamic façade strategies.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Figure 21 provides a comparison of their expected performance. Empirical relationships were extrapolated and interpolated from a range of steady-state CFD results; these were in agreement with expected trends and could thus be used to predict ventilation performance behaviours under conditions that were not simulated (Spentzou et al, 2019). Higher wind speeds enhance the cooling performance of the cross-ventilation, wind-catcher, and dynamic façade strategies.…”
Section: Discussionmentioning
confidence: 70%
“…Steady-state simulations investigated the typical dry-bulb temperature (26°C), under low-average-highest wind speeds (buoyancy, 3.6 and 7 m/ s) and three wind directions, in response to a climate study performed. Further CFD modelling details are described in Spentzou et al (2019), including internal/external domains, mesh sensitivity studies, turbulence model, convergence criteria used and validation of the code. Further, the performance of low-energy retrofits in the case study using dynamic thermal modelling (DTM) was investigated, in order to predict the temporal changes in indoor air quality within specific zones over cooling period in a typical year (i.e.…”
Section: Simulation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the work by Spentzou et al (2017), exploratory thermal modelling simulations performed identified the most suitable wind-catcher design and operation of its openings. Windcatcher tower height increments of 0.5m and up to 2m above and below were investigated; the taller towers delivered higher ventilation rates, although to a small degree.…”
Section: Four-directional Wind-catcher [Wc]mentioning
confidence: 99%
“…Cross-partitions on 'X' arrangement (5m length) facilitate simultaneous inflow and upwards escape of stale air. A four-sided wind-catcher design with a top horizontal covering surface (see Figure 3), was favoured because it could utilise all available wind directions and mitigate against any negative impact of the surrounding buildings on the ventilation performance of the wind-catcher (Spentzou et al, 2017).…”
Section: Four-directional Wind-catcher [Wc]mentioning
confidence: 99%